Cost Estimates of Producing Sugar Apple (Annona squamosa L.) in South Florida - Fredy H. Ballen; Aditya Singh; Edward A. Evans; Jonathan crane (EDIS)
Because of the growing interest in alternative tropical fruit crops to diversify farm income, this 6-page fact sheet written by Fredy H. Ballen, Aditya Singh, Edward Evans, and Jonathan Crane and published by the UF/IFAS Food and Resource Economics Department offers an estimate of costs and returns associated with operating an established sugar apple orchard in south Florida. http://edis.ifas.ufl.edu/fe1053